A Hostile Sports Media?: Perceived Nationalism Bias in Online Sports Coverage. (December 2017) - Kim, Youngju; Billings, Andrew C.
This study examines how perceptions of a story can be altered simply by manipulating the reported winner or loser of a sports contest as well as how individual perceptions of a sports story change when the story is written by a perceived in-group (home nation) versus a perceived out-group (opposing nation). Using a combination of social identity, self-categorization, and hostile media theories, this experimental research aids the understanding of the role nationalism plays in how audiences respond to media gatekeepers from different nations. Results from 219 American participants revealed that the effect of nationalism strength on hostile media perception is greater when the national team loses than when a team wins a game. In addition, the interaction effect of nationalism and game results on the news bias perception is greater when the news is reported in a foreign newspaper than in a domestic newspaper.